Imagining Incarnation: Immanence semper processus in Patrick White’s Voss - McCredden, Lyn (Journal for the Academic Study of Religion, 2022)
What role can the imagination and literary language play in understanding ‘the sacred’, specifically theologies of incarnation? Australian novelist Patrick White’s Voss is read, in this article, as a testing ground for the ways in which human imagination can nurture incarnational longings and beliefs; but also for registering the limits of human language confronting what can be experienced semper processus. That is, this article argues that knowledge of sacredness and the incarnational, diversely intuited in many different forms and practices—Indigenous, European, Romantic, and in the land—can be approached in literary works, but that grasping a key expression of the sacred, incarnation, will always be an agonistic, stumbling, partial human process. The figure of Voss, lonely, self-absorbed, foreign, driven by will, intends to map the country, but this novel unravels human arrogance, undoing all its characters as they reach in their own ways towards incarnational truths.